Quality evaluation of the spatial characteristics of basic public services: a case study of people with disabilities in China between 2012 and 2021 - Yuan, Dan; Guo, Jiapei (Frontiers in Public Health, 2025)
BackgroundUnder the social development goal of realizing common wealth, scientific evaluation and revealing the changing law of the quality of basic public services for people with disabilities is of great significance in promoting the sustainable and healthy development of the cause of people with disabilities.MethodsThis paper constructs a comprehensive evaluation index system of the quality of basic public services for people with disabilities including 20 indicators in 5 dimensions of rehabilitation, education, facilities, culture and sports, and law, and applies the entropy value method and Dagum’s Gini coefficient to measure and compare the quality of basic public services for people with disabilities at the national, regional, and provincial levels in the period of 2012–2021.Results(1) the quality of basic public services for persons with disabilities in China has been steadily improving since 2012, but the overall differences have a tendency to gradually widen, and such differences mainly come from the contribution of inter-regional differences, especially the eastern-western differences. (2) With the exception of the Northeast, the quality index of basic public services for persons with disabilities in the three major regions has been on an upward trend, with the western region showing the fastest rate of improvement. The quality of basic public services for persons with disabilities is highest in the East, but intra-regional differences are the greatest. (3) There are significant spatial differences in the quality of different types of basic public services.ConclusionFrom 2012 to 2021, the provinces with high scores in the quality of basic public services for people with disabilities in China were mainly located in the economically developed eastern coastal areas, while most provinces in the central and western regions have deficiencies in rehabilitation, education, and cultural and sports services. The quality of each service is mostly at a low level and the matching degree is low. Suggestions have been put forward to improve the quality of basic public services for people with disabilities, including strengthening integration with social needs and addressing shortcomings in regional development.